EFFICACY OF NEEM OIL FOR THE ERADICATION OF AQUATIC INSECTS IN FISH NURSERIES - SHRIMALI, SUMANA; RATHORE, ABHIMANYUE SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Generally, the survival rate of carp spawn during the nursery phase is very low due to the presence of harmful aquatic insects in fish nursery pond, which prey heavily upon the spawn and early stages of fry. Insects usually found in large numbers in ponds over the greater part of the year especially during and after rains. They injure the spawn and some of them prey upon spawn. Insects should be eradicated prior to stocking to ensure maximum survival of the spawn. Aquatic insects and their larvae compete for food with the young fish and also cause large scale destruction of hatchlings in nurseries. A study was carried out by the authors to investigating the possible use of natural chemical Neem Oil for the control of aquatic insects in nursery ponds. Bioassay studies were conducted in 5 glass aquaria and using four concentration 0.003, 0.004, 0.005, 0.006 ppm of Neem Oil (natural chemical) on four experimental insects Notonecta(Backswimmer), Dragonfly Nymph, Eretes (Small beetle), Nepa (Water Scorpion). The LC50 value of Neem Oil for the experimental insects (Notonecta, Dragonfly Nymph, Small beetle, Water Scorpion) ranged 0.0033 ppm for Eretes and Nepa at 6 hrs and 0.0040 for Notonecta at 5 hrs. Further, the results on toll rate showed that Backswimmer, Small beetle, Water Scorpion killed within 6hrs when exposed to a concentration of 0.004 ppm Neem oil. This was the lowest dose of Neem oil which killed the predatory insects within the desired period of 6 hrs and the death rate of fish seed at this dose is zero. Therefore, the use of Neem oil @0.004 ppm is recommended for the eradication of predatory insects from fish nursery ponds.